Future Time Perspective in Occupational Teams: Do Older Workers Prefer More Familiar Teams? - Gärtner, Laura U. A.; Hertel, Guido (Frontiers in Psychology, 2017)
Working in teams is quite popular across different industries and cultures. While some of these teams exist for longer time periods, other teams collaborate only for short periods and members switch into new teams after goals are accomplished. However, workers’ preferences for joining a new team might vary in different ways. Based on Carstensen’s socioemotional selectivity theory, we predict that emotionally meaningful teams are prioritized when occupational future time perspective (OFTP) is perceived as limited. Building and expanding on studies outside of the work context, we expected that older as compared to younger workers prefer more familiar teams, and that this effect is mediated by workers’ OFTP. Moreover, we assumed that experimentally manipulated OFTP can change such team preferences. The hypotheses were tested in an online scenario study using three experimental conditions (within-person design). Four hundred and fifty-four workers (57% female, age M = 45.98, SD = 11.46) were asked to choose between a familiar and a new team in three consecutive trials: under an unspecified OFTP (baseline), under an expanded OFTP (amendment of retirement age), and under a restricted OFTP (insolvency of the current company). Whereas the baseline condition was always first, the order of the second and third conditions was randomized among participants. In the baseline condition, results showed the expected mediation effect of workers’ OFTP on the relation between workers’ age and preference for a familiar over a new team. Higher age was associated with more limited OFTP, which in turn was associated with higher preference for a familiar over a new team. Moreover, experimentally restricting OFTP increased preference for a familiar team over a new team regardless of workers’ age, providing further evidence for the assumed causal processes and showing interesting avenues for practical interventions in occupational teams.